Biological Immune Suppression Activity of Protein Peptide in Oyster Survived in Guangxi, China - Chen, Yanhua; Li, Chaozhu; Chen, Yanhui; Zhu, Shuyu; Li, Danrong; Jiao, Shufei (Asian Journal of Chemistry, 2013)
In this paper, the biological immune suppression activity of protein peptide in oyster survived in Guangxi, P.R. China was investigated. The spleen lymphocyte proliferation of mouse influenced by oyster bioactive peptides was observed from MTT assay, lymphocyte proliferation test in vitro inhibition, lymphocyte proliferation of mice in vitro activity, respectively. After the rat spleen lymphocytes was influenced by oyster bioactive peptides, the changes of cytokines IL-2, IFN-g secreted the supernatant of which was detected by ELISA. It was shown that oyster bioactive peptides played an important role in immunosuppressive effects of lymphocyte proliferation. The immunosuppressive effects could be influenced by the concentration of oyster active peptide. Furthermore, the decrease of the secretion of cytokines IL-2 and IFN-g was observed as the presence of oyster active peptide. It is suggested that the oyster bioactive peptides exhibit an efficient immunosuppressive biological activity. Significantly, the efficient oyster bioactive peptides can be developed to an immunosuppressive drug with perfect prospect.